2016
DOI: 10.1111/idh.12241
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ self‐efficacy and children's oral health

Abstract: The Spanish SESMO scale had similar internal consistency and validity as the previously validated English SESMO scale. Mothers' self-efficacy was associated with children's dental status in deciduous dentition but not with children's status in permanent dentition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The characteristics of the 35 selected studies are presented according to the age group and type of study. Table presents the main characteristics of the 7 cohort studies: 5 involving children and 2 involving early adolescents; one case–control study in children; and 27 cross‐sectional studies: 14 involving children and 13 involving early adolescents. The sample sizes varied from 32 to 981 in children and from 100 to 2014 in adolescents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of the 35 selected studies are presented according to the age group and type of study. Table presents the main characteristics of the 7 cohort studies: 5 involving children and 2 involving early adolescents; one case–control study in children; and 27 cross‐sectional studies: 14 involving children and 13 involving early adolescents. The sample sizes varied from 32 to 981 in children and from 100 to 2014 in adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies in children and adolescents were conducted in schools. The protective psychosocial factors investigated were as follows: health locus of control (12 studies), self‐efficacy (11 studies), sense of coherence (10 studies), social support (5 studies), self‐esteem (3 studies), and social network (2 studies). Coping, resilience, family functioning, self‐concept, and optimism were assessed in one study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Information about oral health‐related variables was acquired from clinical assessments performed in caregivers and their children. Information about caregivers' social status, knowledge, and oral health‐related self‐efficacy were acquired from a structured questionnaire …”
Section: Methodsmentioning
confidence: 99%
“…Lower education levels and social status of caregivers were associated with irregular child visits and poor access to dental professional services . A Mexican study showed that mothers' self‐efficacy was associated with their children's oral health …”
Section: Introductionmentioning
confidence: 99%